Microsimulation of impacts of tax and transfer in Viet Nam: Feasibility study - Duong Anh Nguyen; Minh Binh Tran; Anh Mai Le (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper assesses the feasibility of simulating the distributional impacts produced by various tax and transfer instruments in Viet Nam. Viet Nam's system of tax and transfer policies underwent frequent changes, in terms of diversity and adjustment scope. The most important source of data is the Viet Nam Household Living Standards Survey. Investigation of the survey data shows the wide-ranging feasibility of simulating tax and benefit instruments, though more details are available for transfer instruments. The microsimulation should thus focus more on the transfer instruments, which invites interests from a range of government agencies, international organizations, and non-governmental organizations.
Keywords: C15; D04; D31; H21; H24; H53; 330; microsimulation; tax; transfer; distributional impact; Viet Nam